A Rare Association of Thrombotic Thrombocytopenic Purpura with Systemic Lupus Erythematosus in a Sudanese Woman: Case Report - Ibn Idris Rodwan AA (Dove Medical Press, 2021)
Amel Awad Ibn Idris Rodwan,1 Osama Khder Ahmed Elmansour,1,2 Amar F Eldow Ahmed,3 Elnour Mohammed Elagib,1,4 Noha Ibrahim Ahmed Eltahir,4,5 Abubaker Hassan,6 Sara M El-Sadig,7 Abdel Gaffar Abdel Allah Mohammed,8 Huyam H Awadalla,9 Abubakr Abdalwahab Mohammed,5 Mohammed Elmujtba Adam Essa6,10 1Department of Rheumatology, Sudan Medical Specialization Council, Khartoum, Sudan; 2Department of Rheumatology, Faculty of Medicine, Shendi University, Shendi, Sudan; 3Department of Internal Medicine, Wayne State University, Detroit, MI, USA; 4Department of Rheumatology, Omdurman Military Hospital, Khartoum, Sudan; 5Department of Medicine, Faculty of Medicine, Karary University, Khartoum, Sudan; 6Department of Clinical Medicine, Medical and Cancer Research Institute, Nyala, Sudan; 7Department of Medicine, Faculty of Medicine, University of Khartoum, Khartoum, Sudan; 8Rheumatology Department, Security Forces Hospital, Makkah, Saudi Arabia; 9Department of Internal Medicine, Detroit Medical Centre, Detroit, MI, USA; 10Faculty of Medicine, Al Fashir University, Al Fashir, SudanCorrespondence: Mohammed Elmujtba Adam EssaDepartment of Clinical Medicine, Medical and Cancer Research Institute, Nyala, SudanTel +249-90-700-938Email Awadali818@yahoo.comAbstract: Thrombotic thrombocytopenic purpura (TTP) is an uncommon life-threatening condition characterized by hemolytic disorders. The coexistence of systemic lupus erythematosus (SLE) with TTP is extremely rare, although Africans are at increased risk due to inherited risk factors. This report describes a rare clinical manifestation of TTP associated with SLE in a Sudanese patient. A 41-year-old Sudanese woman presented to the emergency department with symptoms and features that were suggestive of malaria, for which she had been treated accordingly. However, a few days later she complained of fever, and was found to have a body temperature of 39.5°C, jaundice, anemia, and thrombocytopenia. Soon after admission, she developed confusion and unrecordable blood pressure. After the patient had stabilized, clinical assessment, immune-system investigation (antinuclear antibody profile, complements, blood panel), and imaging revealed a diagnosis of TTP associated with SLE. The patient received imipenem 500 mg, five sessions of plasmapheresis (60 mL/kg), methylprednisolone 1 g pulse for 3 days, and rituximab 375 mg/week. Three weeks later, the patient was discharged after her condition had improved, and she is now on regular follow-up.Keywords: TTP, SLE, African female, rituximab and plasmapheresis